Dry Biomass and Volatile Oil Production of Achyrocline satureioides Subjected to Agronomic Management Practices - Garcia, Daniel; Wu, Ya-ni; Furlan, Marcos Roberto; Hassani, Danial; Khalid, Muhammad; Huang, Danfeng; Ming, Lin Chau [UNESP] (Springer Nature, 2021)
The scarcity of agronomic protocols for the cultivation of Achyrocline satureioides (Lam.) DC., Asteraceae, in Brazil is reflected by the nonstandardized dry biomass yields and volatile oil contents as well as the chemical composition. The dry biomass, volatile oil contents, and chemical substances of the first Brazilian variety of A. satureioides (CPQBA 2) were analyzed from branches and inflorescences of plants subjected to several organic fertilizer levels in conjunction with two plant and row spacing schemes at 457 days after transplanting. The 30 t/ha of organic fertilizer treatment in conjunction with a spacing of 50 × 50 cm increased the height and dry biomass yield of branches, whereas the 0 t/ha of treatment in conjunction with 50 × 50 cm promoted the largest dry biomass yield of inflorescences. The volatile oil content in the inflorescences was significantly higher in the 30 t/ha of organic fertilizer treatment in conjunction with 50 × 50 cm spacing than in the other treatments. Thirty substances were identified in the volatile oil, among which α-pinene was the major substance in the oil from both plant structures, followed by β-caryophyllene and α-humulene. Thus, the agronomic management practices presented in this study could be useful for producers in attempts to cultivate a local variety of A. satureioides (CPQBA 2). Graphical abstract: [Figure not available: see fulltext.]
Keywords: Cultivation stages; Medicinal plant; Phytochemicals; Phytopharmaceutical industry; Raw material; Tea industry